Study of Low-Salinity Waterflooding for Sandstone Reservoir - Cesarian, Dwiky Pobri (UIN Fatmawati Sukarno Bengkulu, 2019)
Recent studies showed that salinity concentration of the injected water is more important factor rather than the amount of water injected. The objectives of this study are to analyse the effect of salinity and its behaviour in waterflooding and calculating the recovery factor of the oil produced in sandtone reservoir condition. This study focuses on analysing the effect of salinity to its recovery factor, relative permeability, breakthrough time and water cut of the oil-water system. Laboratory experiment had been carried out to determine the recovery factor by using sandstone core with the dimension length and diameter of 3 in and 1.5 in, respectively. Sodium Chloride (NaCl) was used to control the salinity concentration in waterflooding with range of 1,000 ppm to 14,000 ppm. The experiment was run with constant flow rate, pressure and temperature. In this experiment, deionized water with varied salinity and paraffin oil were used to perform the waterflooding procedure. Based on the results obtained, the highest total oil recovery by waterflooding was 57.8% with 4,000 ppm as the optimum salinity, which is 14.6% higher than oil recovered by 14,000 ppm. The results also showed the change in end-point value of relative permeability. It also showed that water cut tend to increase as the salinity increase, while breakthrough time tend to decrease as the salinity increase.